Plasma‐assisted molecular beam epitaxy growth diagram of InGaN on (0001)GaN for the optimized synthesis of InGaN compositional grades (Phys. Status Solidi B 4/2016). Issue 4 (April 2016) - Hestroffer, Karine; Lund, Cory; Li, Haoran; Keller, Stacia; Speck, James S.; Mishra, Umesh K.
Abstract : InGaN alloys have been attracting tremendous interest because of the large range of wavelengths covered when tuning the In to Ga ratio, offering extensive band gap engineering possibilities as well as the opportunity to achieve longer wavelength optoelectronic devices. Industrialization of InGaN materials with large In contents is however still limited by challenges imposed by intrinsic material properties. At typical InGaN growth temperatures the In desorption rate is lower than the In–N bond decomposition rate, making it difficult to avoid accumulation of metal In droplets on the surface. Hestroffer et al. (pp. 626–629 ) have established a growth diagram for InGaN grown on (0001) GaN at a constant temperature of 575 °C versus Ga and In fluxes. The authors identify different regimes, namely: N‐rich, intermediate In‐rich, droplet‐accumulation In‐rich, and Ga‐rich. Compositionally graded InGaN layers are grown by ramping the In and Ga fluxes in parallel under two distinct growth regimes. Structural and optical properties of the two types of grades are compared. The growth diagram proves to be a useful tool in controlling the metal fluxes and thereby the stoichiometry conditions on the surface during the growth of compositionally graded layers.